A Pengaruh Variasi Fraksi Volume Komposit Serat Akar Wangi (Vetiveria Zizanioides) Dan Serbuk Genteng Dengan Resin Polyester Terhadap Uji Ketahanan Bakar - Sutrisno . (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2025)
Natural fiber reinforced composites have advantages as composite reinforcement, namely having a relatively light density and strength and stiffness are also quite high. In this study the authors made specimens using natural fibers in the form of vetiver fiber (vetiveria zizanioides) as composite reinforcement and added tile powder as filler, tile powder has good compounds to strengthen the resulting composite. The purpose of this study was to test the combustion resistance of vetiver fiber reinforced composites and roof tile powder with polyester resin as the matrix. This composite is made by hand lay up technique with variation of volume fraction of vetiver fiber 0%, 5%, 10%, 15%, 20%, roof tile powder 20%, 15%, 10%, 5%, 0%, 80% polyester resin with random fiber orientation. Combustion resistance testing was conducted according to ASTM D-635 standard. The results of this study indicate that composites with volume fractions (20%, 0%, 80%) make this composite flammable, namely with an average Time Of Burning value of 26.52 seconds. While composites with volume fractions (0%, 20%, 80%) are composites that have the most fire-resistant properties with an average Rate Of Burning value of 18.723 mm/min. Composites with a lot of vetiver fiber composition have a faster ignition process, while composites that are only given tile powder filler have a longer ignition process. Meanwhile, the more vetiver fiber composition, the faster the process of ignition.